Role of Information Communication Technology in Accelerating the Sustainable Development Goals in Financial Inclusion - Elmira Siska; Dante Rio Sebastian (Forum Kerjasama Pendidikan Tinggi, 2022)
The UN has assigned Sustainable Development Goals (SDGs) as a framework for development agendas and political strategies for the next 15 years. To accomplish the SDGs, both developed and developing countries must adopt the SDGs. SDGs consist of 17 goals that address a wide variety of sustainable development issues. The objective of this study was to analyze the roles of ICT in accelerating the achievement of the SDGs, to investigate in which number of SGDs the ICT can be utilized to accelerate financial inclusion, and to identify the success factors toward ICT-enabled financial inclusion. This study employed a qualitative research design by using a systematic literature review (SLR) approach. Secondary data gathered from various resources related to the research topic, such as national journals, international journals, proceedings, books, reports, and other relevant scientific sources from 2016 to 2022 were used in this study. The finding of the study highlights the importance of ICT in accelerating the implementation in all of the 17 SDGs. In relation to SDGs in financial inclusion, ICT has an essential role in SDG 1 (ending poverty), SDG 5 (gender equality), SDG 8 (small businesses and entrepreneurship), and SDG 9 (sustainable infrastructure). Some factors that affect the success of ICT-enabled financial services include policy framework between financial institutions and mobile providers, adequate financial and technical resources, and, a collaborative effort among banks, operators, and agents.